An H2O Maser survey towards BGPS sources in the Outer Galaxy. (June 2016) - Xi, Hong-Wei; Zhou, Jian-Jun; Esimbek, Jarken; Wu, Gang; He, Yu-Xin; Ji, Wei-Guang; Tang, Xiao-Ke; Yuan, Ye
Abstract: We performed an H2 O maser survey towards 274 Bolocam Galactic Plane Survey (BGPS) sources with 85° < l < 193° using the Nanshan 25 m radio telescope. We detected 25 H2 O masers, and five of them are new detections. The detection rate of H2 O masers in our sample is 9% which is very low. The detection rate of H2 O masers increases as the 1.1 mm flux density of BGPS sources increases, and both the peak flux density and luminosity of H2 O masers increase as the sources evolve. The detection rate of H2 O masers toward BGPS sources without HCO + emission is low. The BGPS sources associated with both H2 O and CH3 OH masers seem to be more compact than those only associated with H2 O masers. This indicates that the sources with both masers may be in a relatively later evolutionary stage. The strongest H2 O maser source G133.715+01.217, also well known as W3 IRS 5 which has a flux density of 2.9×10 3 Jy, was detected at eight different nearby positions. By measuring the correlation between the flux densities of these H2 O masers and their angular distance from the true source location, we get the influence radius r = 1 0.8 log ( F 0 3 rms ) . For our observations, strong sources can be detected anywhere within this radius. It is helpful to determine whether or not a weak maser nearby the strong maser is a true detection.